2001
DOI: 10.1109/20.951056
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Co-C nanodot arrays produced by direct interferometric laser annealing

Abstract: Polushkin, Nikolay; and Salashchenko, N.N., "Ferromagnetic Co-C nanodot arrays produced by direct interferometric laser annealing" (2001 Abstract-Magnetic properties of Co-C nanodot arrays produced by direct interferometric laser annealing are investigated by magnetic force microscopy (MFM) and magnetization measurements. The dots are formed by locally annealing sputtered amorphous Co-C films in regions where the laser intensity is highest. As-sputtered Co-C films do not exhibit ferromagnetic order at room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition, one might ask whether the regions between the dots are magnetic based on the low in-plane coercive field. In fact, we have shown that increasing the laser power leads to a more homogeneously magnetized film, 19 but the present work is in a regime below this threshold. The low H c value is compatible with domain-wall motion but comparing the dot diameter ͑about 250 nm͒ with the Bloch-wall width of Co ͑14 nm͒ suggests that the wall motion may well be confined to a single dot.…”
mentioning
confidence: 82%
“…In addition, one might ask whether the regions between the dots are magnetic based on the low in-plane coercive field. In fact, we have shown that increasing the laser power leads to a more homogeneously magnetized film, 19 but the present work is in a regime below this threshold. The low H c value is compatible with domain-wall motion but comparing the dot diameter ͑about 250 nm͒ with the Bloch-wall width of Co ͑14 nm͒ suggests that the wall motion may well be confined to a single dot.…”
mentioning
confidence: 82%
“…The synthesis of magnetic nanodots either in matrix or onto substrate has been an interesting subject because of increasing demand of magnetic recording media and magnetic devices (1,2). Several groups have fabricated magnetic nanodots (3)(4)(5) and many methods have been adopted to fabricate nanodots arrays such as, ion beam (6) or indirect (7-9) lithography and interferometric laser (10,11). Ferromagnetic nanodots arrays have been investigated by numbers of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional laser interference lithography is a multi-step process, involving the interference of several laser beams, use of photoresist, etching and subsequent cleaning when applying it to pattern magnetic structures [2,5]. Moreover, in the preparation of the film process using interference lithography, what the related factors with the magnetic properties of thin films, and how to obtain the micro/nano-structure and excellent magnetic properties of thin films will lay a good foundation for the preparation and study of magnetic film devices.…”
Section: Introductionmentioning
confidence: 99%